Pengaruh Strategi Pembelajaran dan Gaya Berpikir Terhadap Hasil Belajar Sejarah Siswa SMA - Lukman Nadjamuddin; I Nyoman Sudana Degeng; Wasis Djoko Dwiyogo; Muhammad Nur Ali (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
This study aims to determine the effect of group investigation learning strategies and expository learning strategies on historical learning outcomes, the effect of vertical and lateral thinking styles on historical learning outcomes, and the influence of the interaction between learning strategies and thinking styles on historical learning outcomes. This study used a quasi-experimental design with a 2x2 factorial version of the pretest posttest nonequivalent control group design. The research subjects were students of class XI at three public high schools in Sigi Regency who were selected by the cluster random sampling method. Subjects were involved as many as 112 people who were divided into six classes. The research data were collected using thinking style instruments and learning outcomes tests and hypothesis testing was carried out at the 5% significance level. The results showed the following findings: 1) descriptively, the group investigation learning strategy was superior to the expository learning strategy in increasing the learning outcomes of history; 2) the student group has a vertical thinking style, has superior historical learning outcomes compared to the student group who has a lateral thinking style; and 3) there is an interaction effect between learning strategies and thinking styles on historical learning outcomes. The results of this study informed that the group investigation learning strategy had a significant effect on history learning outcomes depending on students' thinking styles.